Monitoring and evaluating the payment-for-performance premise of REDD+: the case of India's ecological fiscal transfers. Issue 7 (3rd July 2018) - Busch, Jonah
ABSTRACT: Introduction: The central premise underlying international payments for Reducing Emissions from Deforestation and forest Degradation (REDD+) is that offering governments ex post payments for verified success in reducing emissions will motivate them to protect and restore forests. However, the extent to which performance-based payments motivate governments to protect and restore forests has yet to be evaluated quantitatively. Researchers have only quantitatively evaluated performance-based payments to non-governments for forest outcomes (e.g. payments for ecosystem services) and to governments for non-forest outcomes (e.g. results-based aid). Methods: We describe how researchers now have an opportunity to more easily evaluate performance-based payments to governments for forest outcomes thanks to India's new ecological fiscal transfers (EFTs), which provide $6-12 billion per year to Indian states in proportion to their forest cover. Discussion: India's EFTs differ from REDD+ programs in that they pay for states' stock of forest area in the recent past rather than reductions in the rate of forest carbon loss in the near-future. Nevertheless, India's EFTs focus on a single outcome and have many recipient governments, significant financial scale, lack of contemporaneous confounding policy changes, universal participation, and long-term data collection. Conclusion: These features make India's EFTs especially useful for testing the payment-for-performance premise of REDD+.